Answer 1 / 25
Step-by-step explanation:
The probability that the first
of the three mutants will take over the population = 2 / 100
The probability that the second
of the three mutants will take over the population = 1.01 / 100
The probability that the third
of the three mutants will take over the population = 0.99 / 100
Therefore, the probability that each of the three mutants will take over the population = probability of the first,second or third = 2 / 100 + 1.01 / 100 + 0.99 / 100 = (2+1.01+0.99)/100 = 4 / 100 = 2/25
Answer:
-1
Step-by-step explanation:
m = y2 - y1 / x2 - x1
= 1 - 4 / 8 - 5
= -3 / 3
= -1
<span>4[(10-4) 2 to the second power divided by 4]
=4x6x2</span> to the second power divided by 4
=6x2 to the second power
=6x4
=24
Hope that helps and hope that I didn't misunderstand your question
The answer is 12 because it is a negative
Answer: 107
Step-by-step explanation: